Determination of stress state based on well logging data and laboratory easurements – a CBM well in the southeastern part of the Upper Silesian Coal Basin (Poland) - Kępiński, Michał (Geology, Geophysics and Environment, 2020)
The main objective of this study is to present calculation methods of horizontal stress profiles, taking into account the stress boundaries model, poro-elastic horizontal strain model and the effective stress ratio approach, using calibration with wellbore failure. The mechanical earth model (MEM) parameters from log measurements and well testing data were estimated for a well located in the southeastern part of the Upper Silesian Coal Basin. Log-derived horizontal stresses of the well are commonly treated as the final product of geomechanical modeling in oil and gas practices. A less popular method for estimating horizontal stresses is based on Kirsch equations juxtaposed with compressional and tensile failure observed on a micro-imager or six-arm caliper. Using this approach, horizontal stresses are determined based on the fact that when hoop stresses exceed the formation’s tensile strength, tensile fractures are created, and when those stresses exceed the compressive strength of the formation, breakouts can be identified. The advantage of this method is that it can be run without in situ stress measurements. The presented workflow is recommended every time there is an image log and dipole sonic measurement in the available dataset, both being necessary to observe the failure zones and MEM.